2010
DOI: 10.3133/ofr20101167
|View full text |Cite
|
Sign up to set email alerts
|

A method for quantitative mapping of thick oil spills using imaging spectroscopy

Abstract: thickness, we estimate that the volume of oil, including oil thicker than can be probed in the AVIRIS imagery, is possibly as high as 150,000 barrels in the AVIRIS scenes. When this value is projected to the entire spill, it gives a volume of about 500,000 barrels for thick oil remaining on the sea surface as of May 17. AVIRIS data cannot be used to confirm this higher volume, and additional field work including more in-situ measurements of oil thickness would be required to confirm this higher oil volume. Bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
137
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(140 citation statements)
references
References 16 publications
3
137
0
Order By: Relevance
“…The remote sensing effort of the NASA ER/2 equipped with Airborne Visible InfraRed Imaging Spectrometer (AVIRIS) surveyed about 30% of the core area of the surface spill on May 17, 2010. Extrapolating the examined area to the whole slick, Clark et al (2010) estimated that a minimum of floating oil of between 66,000 and 120,000 bbl. Limitations of the instruments do not allow measurement of very thick oil.…”
Section: Previous Experience -The Ixtoc Spillmentioning
confidence: 99%
“…The remote sensing effort of the NASA ER/2 equipped with Airborne Visible InfraRed Imaging Spectrometer (AVIRIS) surveyed about 30% of the core area of the surface spill on May 17, 2010. Extrapolating the examined area to the whole slick, Clark et al (2010) estimated that a minimum of floating oil of between 66,000 and 120,000 bbl. Limitations of the instruments do not allow measurement of very thick oil.…”
Section: Previous Experience -The Ixtoc Spillmentioning
confidence: 99%
“…The goal when building the spectral libray was to reproduce the observations presented in (Clark et al, 2010) and to extend the measurements on other products. The library includes the transmittance and reflectance spectra of thin layers of seven mineral…”
Section: A Spectral Librarymentioning
confidence: 99%
“…Hyperspectral remote sensing has shown some interesting results in the VNIR range (400 to 1000nm) for a rough estimation of thickness and the evaluation of volume at sea using airborne sensors (Lennon et al, 2006, Otremba and Piskozub, 2004, Wettle et al, 2009. During the Deepwater Horizon oil spill, Clark et al (2010) have shown in (Clark et al, 2010) the high potential of hyperspectral data in the SWIR range (1000nm to 2500nm) for the estimation of high thickness ranges (over a millimetre) and emulsion rates. They proceed by associating shape parameters of reflectance spectra of the data to those from a spectral library.…”
Section: Introductionmentioning
confidence: 99%
“…Work from Clark (Clark, 2010), Sicot (Sicot 2014) and others seem to indicate that the NIR-SWIR domains (0.7 -2.5 µm wavelength) offer better opportunities to detect and characterize thick oil slicks. This paper will focus on this domain.…”
Section: Introductionmentioning
confidence: 99%